A literature review of sleep problems and neurodevelopment disorders - Al Lihabi, Abeer (Frontiers in Psychiatry, 2023)
Abstract Introduction: Sleep is an incredibly complex process that goes beyond relaxing and body resting. Disturbance in sleep leads to several short-term and long-term consequences. Neurodevelopmental diseases such as "autism spectrum disorder" (ASDs), Attention-deficit hyperactivity disorder (ADHD), and intellectual disability commonly experience sleep disorders that affect their clinical presentation, daily function, and quality of life. Discussion: The incidence of sleep problems in ASD patients ranges from 32 to 71.5 %, especially insomnia, while an estimated 25% to 50% of people with ADHD report having sleep issues in clinical settings. The incidence of sleep issues is widespread in persons with intellectual disabilities, reaching up to 86%. This article is a literature review covering the neurodevelopmental disorder interaction with sleep disorder and different management. Conclusion: Disorders of sleep are key concerns in children with neurodevelopmental disorders. In this group of patients, sleep disorders are common and tend to be chronic. Recognizing and diagnosis of sleep disorders will enhance their function, response to treatment, and quality of life. Keywords: Autism spectrum disorders, ASD, Sleep, Electroencephalography, Actigraphy, Attention-deficit hyperactivity disorder